Regulation of viral gene expression by duck enteritis virus UL54 - Chaoyue Liu (Nature Portfolio, 2017)
Abstract Duck enteritis virus (DEV) UL54 is a homologue of human herpes simplex virus-1 (HSV-1) ICP27, which plays essential regulatory roles during infection. Our previous studies indicated that DEV UL54 is an immediate-early protein that can shuttle between the nucleus and the cytoplasm. In the present study, we found that UL54-deleted DEV (DEV-ΔUL54) exhibits growth kinetics, a plaque size and a viral DNA copy number that are significantly different from those of its parent wild-type virus (DEV-LoxP) and the revertant (DEV-ΔUL54 (Revertant)). Relative viral mRNA levels, reflecting gene expression, the transcription phase and the translation stage, are also significantly different between DEV-ΔUL54-infected cells and DEV-LoxP/DEV-ΔUL54 (Revertant)-infected cells. However, the localization pattern of UL30 mRNA is obviously changed in DEV-ΔUL54-infected cells. These findings suggest that DEV UL54 is important for virus growth and may regulate viral gene expression during transcription, mRNA export and translation.